STOCHASTIC MODEL FOR GOLD PRICES AND ITS APPLICATION FOR NOARBITRAGE PRICING - Issaranusorn, N.; Rujivan, S.; Mekchay, K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, we develop a onefactormodel of stochastic behavior ofgold prices. The gold prices are assumed to follow an extended Geometric BrownianMotion with a timevaryingdrift which describes seasonal variation in gold prices.The drift includes instantaneous convenience yields which follow an ordinary differentialequation. Moreover, we derive closedformsolutions for noarbitragepricesof gold futures and European gold options under the noarbitrageassumptions.